Mechanism of paraquat resistance in crassocephalum crepidioides (Benth.) S. moore during immature stage - B. S., Ismail; T. S., Chuah; H. H., Khatijah (Universiti Putra Malaysia Press, 2004)
The mechanism of paraquat resistance in Crassocephalum crepidioides at the six-leaf stage was investigated. The extractable paraquat was not metabolized fly the leaf tissue in the resistant (R) and susceptible (S) biotypes. Therefore, differential metabolism does not appear to play a role in the mechanism of resistance. The S biotype absorbed 44% more 14Gparaquat than the R biotype. However, more than 98% of the absorbed 14G paraquat remained on the treated leaf of both biotypes. The difference in absorption had a negative correlation with the amount of epicuticular wax as well as the cuticle of leaf surfaces in both biotypes. The results of this study suggest that differential absorption may be a factor that accounts for resistance to paraquat at the six-leaf stage.